NanoCity: An Immersive Game to Transform Student Perceptions of Science - Murcia, Karen; Paul Newhouse, C.; Boston, J. (Springer International Publishing, 2018)
This chapter reports on the design and trial of a virtual reality transformational game aimed at promoting the study of nanotechnology among secondary science students. Nanocity is a prototype game purposefully designed to create an engaging and immersive learning environment. The game was tested with 87 lower secondary students in two Western Australian schools. After the experience, these students were surveyed and some participated in focus group interviews. These data, along with observation of the students using the game, provided evidence that the experience was not only engaging but had a transformational effect on the attitudes and perceptions of students towards nanotechnology as a field of study and work. These results supported the suggestion that transformational games can be used to support the learning of students in science and in particular improve their attitudes and perceptions of future engagement with science.